Targets, Interest Rates, and Household Saving in Urban China - Nabar, Malhar (IMF Working Papers; Working Paper ;, 2011)
This paper studies a panel of China's provinces over the period 1996-2009 during which urban household saving rates increased from 19 percent of disposable income to 30 percent. It finds that the increase in urban saving rates is negatively associated with the decline in real interest rates over this period. This negative association suggests that Chinese households save with a target level of saving in mind. When the return to saving declines (increases), it becomes more difficult (easier) to meet a target and households increase (lower) their saving out of current disposable income to compensate. The results are robust across specifications and to the inclusion of additional variables. A main policy implication is that an increase in real deposit rates may help lower household saving and boost domestic consumption.